Why do platforms charge proportional fees? Commitment and seller participation - Johannes Muthers; Sebastian Wismer (Johannes Kepler University of Linz, Department of Economics, 2023)
This paper deals with trade platforms whose operators not only allow third party sellers to offer their products to consumers, but also offer products themselves. In this context, the platform operator faces a hold-up problem if he uses classical twopart tariffs only as potential competition between the platform operator and sellers reduces platform attractiveness. Since some sellers refuse to join the platform, some products that are not known to the platform operator will not be offered at all. We find that revenue-based fees lower the platform operator's incentives to compete with sellers, increasing platform attractiveness. Therefore, charging such proportional fees can be profitable, which may explain why several trade platforms indeed charge proportional fees.
Keywords: D40; L14; L81; 330; Intermediation; Platform Tariff; Hold-Up Problem